Spy school goes south: Spy School # 6 : a Spy school novel - Gibbs, Stuart, 1969-; Thompson, Ryan (New York : Simon & Schuster Books for Young Readers, 2018)
Thirteen-year-old spy in training Ben Ripley is sent to Mexico to try to thwart the evil organization, SPYDER--the CIA's main enemy.
Sequel to: Spy school secret service.
Sequel: Spy school British invasion.
new kids book 2023 winter.
"New York Times bestselling author"--Dust jacket.
Ages 8-12.
Keywords: Spies -- Fiction; Adventure and adventurers -- Fiction; Schools -- Fiction; Friendship -- Fiction; Mexico -- Fiction